Influence of leadership on implementing Dementia Care Mapping: A multiple case study. (August 2019) - Quasdorf, Tina; Bartholomeyczik, Sabine
Dementia Care Mapping is an internationally applied method for enhancing person-centred care for people with dementia in nursing homes. Recent studies indicate that leadership is crucial for the successful implementation of Dementia Care Mapping; however, research on this topic is rare. This case study aimed to explore the influence of leadership on Dementia Care Mapping implementation in four nursing homes. Twenty-eight interviews with project coordinators, head nurses and staff nurses were analysed using qualitative content analysis. Nursing homes that failed to implement Dementia Care Mapping were characterised by a lack of leadership. The leaders of successful nursing homes promoted person-centred care and were actively involved in implementation. While overall leadership performance was positive in one of the successful nursing homes, conflicts related to leadership style occurred in the other successful nursing homes. Thus, it is important that leaders promote person-centred care in general and Dementia Care Mapping in particular. Furthermore, different types of leadership can promote successful implementation. Trial registration of the primary study: Current Controlled Trials ISRCTN43916381.